Employee health, coping and methodologies - Perrewe, Pamela L.; Ganster, Daniel C. (Research in occupational stress and well being ;, 2006)
This is an annual research series devoted to the examination of occupational stress, health and well being, with particular emphasis on the multi-disciplinary nature of occupational stress. The intent is to pull together the various streams of research from a variety of disciplines to better capture the significant bodies of work in occupational stress and well being. A multidisciplinary and international perspective is provided to give a thorough and critical assessment of issues in occupational stress and well being. The theme for this volume is: Employee Health, Coping, and Methodologies.